Penerapan Model Pembelajaran Kooperatif Tipe Think-Pair-Share Untuk Mengembangkan Sikap Sosial Siswa Kelas X SMA Negeri 8 Makassar - Sulfikar; Muhammad Anwar; Fahrul Islam (Jurnal Ilmiah Kanderang Tingang, 2018)
This research aims to know the social attitude of students after the implementation of cooperative learning model type think-pair-share (TPS) on sub topic hydrocarbon. The design of research is a one-shot case study. The indicators for the social attitudes studied are politeness, honesty, discipline, responsibility, tolerance, team working, curiosity, and communicative. The research subject is the 34 students of class X5 SMA Negeri 8 Makassar. The student’s social attitude was recorded using observation sheets and peerassessment which both had been content validation. Students’ achievement data was collected using an achievement test that had been content and item validation. The data was analyzed using descriptive statistics. The results shown that the students developed positive social attitudes after experiencing the cooperative learning model type TPS. Generally, each social attitude indicators increased throughout four meetings.